PELATIHAN PERAWATAN WAJAH DAN MAKEUP UNTUK IBU-IBU RT 01 RW 01 SUNGAI PASIR MERAL KARIMUN - Ade Sarmini (Jurnal Pengabdian Ibnu Sina, 2022)
Facial care and make-up training for women from RT 01 RW 01 Sungai Pasir Meral Karimun went through several stages. The first stage is to prepare training products/materials. The next stage is the training which begins with the preparation of the place, the service, the trainer and the participant. The next stage is facial care and make up training. There are 6 steps of facial care and 8 steps of wearing make up during the day and night. The trainer explained in Indonesian and practiced facial care and make-up by choosing participants as models. The next stage is the practice of implementation and evaluation where the women from RT 01 RW 01 Sungai Pasir Meral Karimun also practice facial care and make up using models from their fellow mothers from RT 01 RW 01.